Interface between biomedical and traditional systems of treatment and care among HIV positive fisher folk in two fishing communities on Lake Victoria, Uganda - Christopher, Tumwine; Peter, Aggleton; Stephen, Bell (African Health Sciencies, 2022)
Background: Fisherfolk have been identified as a key population in the HIV response in Uganda due to high HIV prevalence and low engagement in HIV services. While studies have examined lifestyles and risk, much remains to be understood about help and health seeking experiences, including the combined use of biomedical and traditional health care. Objective: To examine the use of biomedical and traditional health care in two fishing communities around Lake Victoria in Uganda. Methods: Exploratory, in-depth qualitative study involving semi-structured interviews with 42 HIV positive fisherfolk. Results: Prior to HIV diagnosis, participants who described becoming ill sought different forms of help including biomedical treatment prescribed by health workers or self-prescribed; biomedical and herbal medicines together; herbal medicines only; or no form of treatment. Following HIV diagnosis, the majority of participants used ART exclusively, while a smaller number used both ART and traditional care strategies, or reported times when they used alternative therapies instead of ART. Prior to HIV diagnosis, fisherfolk’s health care seeking practices inhibited engagement with HIV testing and access to biomedical HIV treatment and care. After HIV diagnosis, most resorted only to using ART. Conclusion: Study findings provide insight into how fisherfolk’s use of biomedical and traditional care prior to diagnosis influences subsequent engagement with HIV treatment. Efforts are needed to reach fisherfolk through everyday health seeking networks to ensure HIV is diagnosed and treated as early as possible.